The Influence of Good Corporate Governance, Corporate Social Responsibility, and Intellectual Capital on Financial Performance in Plantation Sub-Sector Manufacturing Companies Listed on the Indonesia Stock Exchange in 2019-2020: Pengaruh Good Corporate Governance, Corporate Social Responsibility, Dan Intellectual Capital Terhadap Kinerja Keuangan Pada Perusahaan Manufaktur Subsektor Perkebunan Yang Terdaftar Di Bursa Efek Indonesia Pada Tahun 2019 – 2020 - Iktiasari, Firra Mayang; Setiyono, Wisnu Panggah (Universitas Muhammadiyah Sidoarjo, 2022)
The strategy carried out by the company must have strong competitiveness in national and international markets. One of the important goals of establishing a company is to increase the welfare of its owners or shareholders, or maximize shareholder wealth through increasing the value of the company. This study uses a quantitative method, the sample was selected by the purposive sampling method, namely 10 manufacturing companies in the plantation sub-sector, which are listed on the IDX for the 2019-2020 period. The data collection technique uses the company's annual report from the 2019-2020 period. The analytical technique used in this study is path analysis with the help of the Eviews 8 program. The results of this study indicate that Good Corporate Governance has a value of 0.04 < 0.05, Corporate Social Responsibility 0.29 < 0.05, and Intellectual Capital 0.46 < 0.05, which means the variable Good Corporate Governance , Corporate Social Responsibility, and Intellectual Capital have a very significant effect on the performance of manufacturing companies in the plantation sub-sector.